Origins of High Performance and Degradation in the Mixed Perovskite Solar Cells. Issue 8 (7th January 2019) - Heo, Sung; Seo, Gabseok; Lee, Yonghui; Seol, Minsu; Kim, Seong Heon; Yun, Dong‐Jin; Kim, Yongsu; Kim, Kihong; Lee, Junho; Lee, Jooho; Jeon, Woo Sung; Shin, Jai Kwang; et al.
Abstract: The origins of the high device performance and degradation in the air are the greatest issues for commercialization of perovskite solar cells. Here this study investigates the possible origins of the mixed perovskite cells by monitoring defect states and compositional changes of the perovskite layer over the time. The results of deep‐level transient spectroscopy analysis reveal that a newly identified defect formed by Br atoms exists at deep levels of the mixed perovskite film, and its defect state shifts when the film is aged in the air. The change of the defect state is originated from loss of the methylammonium molecules of the perovskite layer, which results in decreased J SC, deterioration of the power conversion efficiency and long‐term stability of perovskite solar cells. The results provide a powerful strategy to diagnose and manage the efficiency and stability of perovskite solar cells. Abstract : The origins of high device performance and degradation in air of mixed perovskite cells are investigated by monitoring defect states and compositional changes of the perovskite layer over time. The results reveal that a defect formed by Br atoms exists at deep levels of the perovskite, and its defect state shifts when the film is aged.